Looking for Safe Haven in a City Torn Apart by War: Narratives of agency from internally displaced persons in the southern Philippines - Quintero, Romeo Joe (Anti-Trafficking Review, 2024)
In this paper, I interrogate the dominant representation of internally displaced persons (IDPs) in humanitarian discourse as helpless victims in need of rescue. Based on the stories of IDP women and gender diverse individuals in the Philippines affected by the Zamboanga City siege in 2013, I illustrate how they exercised agency to shape their trajectories of displacement. The capacity of Filipino IDPs to contend with their displacement is shaped by their power as bakwit (evacuees), and by their class and ethnoreligious identities. While Christian Filipino IDPs had access to material, financial, and social resources, allowing them to engage in temporary migration after displacement, Muslim Filipino IDPs with limited access to these same resources found themselves in unwanted mobility and prolonged situations of displacement. Yet, Muslim Filipino IDPs do not lack agency, as they continue to actively and consciously forge new strategies to regain a sense of home in extended exile. Ultimately, while identifying bakwit power as a useful conceptual tool to make legible how IDPs exercised control at different stages of their displacement, embracing such a framework should not negate the long history of political violence in the region that continues to keep some people on the move.